2011
DOI: 10.1001/archpediatrics.2011.111
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Air Cleaners and a Health Coach to Improve Indoor Air Quality for Inner-City Children With Asthma and Secondhand Smoke Exposure

Abstract: Objective: To test an air cleaner and health coach intervention to reduce secondhand smoke exposure compared with air cleaners alone or no air cleaners in reducing particulate matter (PM), air nicotine, and urine cotinine concentrations and increasing symptom-free days in children with asthma residing with a smoker. Design: Randomized controlled trial, with randomization embedded in study database. Settings: The Johns Hopkins Hospital Children’s Center and homes of children. Participants: Children with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 52 publications
10
168
1
Order By: Relevance
“…However, our findings are likely independent of SHS exposure, and there are other important modifiable sources of indoor PM and NO 2 (20,40). Future studies investigating the effectiveness of environmental interventions aimed at reducing indoor pollutant concentrations in homes of patients with COPD, such air cleaner intervention trials that have shown reduction in indoor PM and improved symptoms in asthma (10), are warranted as potential nonpharmacologic approaches to improving COPD health. They may represent more cost-effective and novel therapeutic arenas for a disease with limited treatment options.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, our findings are likely independent of SHS exposure, and there are other important modifiable sources of indoor PM and NO 2 (20,40). Future studies investigating the effectiveness of environmental interventions aimed at reducing indoor pollutant concentrations in homes of patients with COPD, such air cleaner intervention trials that have shown reduction in indoor PM and improved symptoms in asthma (10), are warranted as potential nonpharmacologic approaches to improving COPD health. They may represent more cost-effective and novel therapeutic arenas for a disease with limited treatment options.…”
Section: Discussionmentioning
confidence: 74%
“…feasible interventions, such as the placement of high-efficiency particulate air cleaners (10), could be used to improve in-home air quality.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] The trials were published between 1994 and 2013. A flowchart describing the identification process is presented in Fig 1. Study characteristics of included trials are presented in Tables 1 and 2. …”
mentioning
confidence: 99%
“…21,22,25,27,33,34,84,85,[87][88][89][90]93,97 Biomarkers Of the 13 studies presenting biomarker information at follow-up, 9 presented urinary cotinine or urinary CCR 20,[23][24][25][31][32][33]93,96 ; 2 presented salivary cotinine 22,26 ; 1 presented serum cotinine 27 ; and 1 presented hair nicotine and cotinine. 21 …”
mentioning
confidence: 99%